Task Design for Cruise English Conversations Based on Job Workflow: A Case Study of Cabin Service - Zhang, Xiaowei; Jiang, Rui (Journal of Educational Research and Policies, 2025)
This study constructs a task-based language teaching (TBLT) model for cabin service English communication, grounded in the workflow analysis of cruise cabin service positions. By dissecting core service scenarios (e.g., room cleaning, special needs response, complaint handling), the research develops a three-dimensional task system integrating linguistic skills, cultural awareness, and service strategies. Supported by authentic cruise service cases, a hierarchical and scenario-based task repository is created, accompanied by a hybrid assessment system combining formative and summative evaluations. Empirical data shows significant improvements in learners’ job-related English proficiency (37.2% increase) and cultural adaptability (91.5% customer satisfaction). This study provides a replicable framework for cruise service English curriculum development.